Effects of plant-based diets combined with exercise training on leptin and adiponectin levels in adults with or without chronic diseases: a systematic review and meta-analysis of clinical studies - Kazeminasab, Fatemeh; Fatemi, Rouholah; Bagheri, Reza; Santos, Heitor O.; Dutheil, Fred (Frontiers in Nutrition, 2024)
The effects of exercise training combined with plant-based diets (PBD) on leptin and adiponectin levels have been studied. However, little is known regarding the impact of exercise training combined with PBD on leptin and adiponectin levels in adults with or without chronic diseases.Methods: PubMed, Web of Science, and Scopus were searched to identify original articles, published until May 2024, to assess the effects of exercise training combined with PBD on leptin and adiponectin levels in adults with or without chronic diseases. Standardized mean differences (SMD) and 95% confidence intervals were calculated using random models.Results: Nine studies comprising 960 participants with overweight and obesity were included in the current metaanalysis. Exercise training combined with PBD reduced leptin [SMD=-0.33 (95% CI: -0.62 to -0.04); p=0.025] while increasing adiponectin [SMD=0.93 (95% CI: 0.12 to 1.74); p=0.024] levels.Exercise training combined with PBD is suggested as a non-invasive intervention for reducing leptin while increasing adiponectin levels to control body mass and other disorders related to obesity in adults.